2017
DOI: 10.1007/978-3-319-58592-5_22
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Centromere Defects in Cancer

Abstract: The accurate segregation of chromosomes to daughter cells is essential for healthy development to occur. Imbalances in chromosome number have long been associated with cancers amongst other medical disorders. Little is known whether abnormal chromosome numbers are an early contributor to the cancer progression pathway. Centromere DNA and protein defects are known to impact on the fidelity of chromosome segregation in cell and model systems. In this chapter we discuss recent developments in understanding the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Indeed it has been demonstrated that as many as 90% of solid organ and 50% of haemopoietic cancers are aneuploid which directly implicates epigenomic centromeric/kinetochore processes in tumourigensis [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed it has been demonstrated that as many as 90% of solid organ and 50% of haemopoietic cancers are aneuploid which directly implicates epigenomic centromeric/kinetochore processes in tumourigensis [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most intriguing things about the pattern of CCA disease to be discussed is the cellular mechanisms which might be responsible. Whilst various disruptions of normal chromosomal physiology were described several decades ago as noted above [ 16 , 27 , 66 , 67 ], major advances in our understanding of the machinery of mitosis and meiosis have occurred in the decades since that time [ 68 , 69 , 70 , 71 , 72 , 73 ] and it would seem obvious from the pairing of trisomic chromosomal disorders with the monosomy of Turners syndrome [ 2 , 8 ] that chromosomal mis-segregation must be involved by some mechanism. However, as explored in some detail in the Discussion section, the exact mechanism of this is not understood in molecular terms.…”
Section: Introductionmentioning
confidence: 99%
“…Defects in centromere-and kinetochore-associated proteins have been proposed to contribute to aneuploidy and chromosomal instability, which are associated with cancer progression in several types of human tumor (24,25). The presence of aneuploid cells is detected in ~90% of solid tumors and ~50% of hematopoietic cancers (26). Chromosomal instability is believed to be the driver of cancer predisposition, progression and intratumoral heterogeneity, whereas aneuploidy and chromosomal instability have been attributed to poor patient prognosis, metastasis and chemotherapeutic resistance (27).…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomes are bound to the growing plus ends of the half spindle rays. The chromosomes separate at anaphase due to the pulling forces exerted by dynein-dynactin molecular motors, which retract the chromosomes toward the minus ends of the microtubules and the new pronuclear poles [108][109][110][111][112][113].…”
Section: Epigenomic Control Of Chromosomal Centromeric Functionmentioning
confidence: 99%